2016
DOI: 10.1101/064519
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local chromosome context is a major determinant of crossover pathway biochemistry during budding yeast meiosis

Abstract: The budding yeast genome contains regions where meiotic recombination initiates more frequently than in others. This pattern parallels enrichment for the meiotic chromosome axis proteins Hop1 and Red1. These proteins are important for Spo11-catalyzed double strand break formation; their contribution to crossover recombination remains undefined. Using the sequencespecific VMA1-derived endonuclease (VDE) to initiate recombination in meiosis, we show that chromosome structure influences the choice of proteins tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 129 publications
2
9
0
Order By: Relevance
“…A recent study suggested the importance of the local axis-enriched context to repair DSBs by the interfering CO pathway (Medhi et al 2016). Consistently, our data identified a link between the ZZS complex and the chromosome axis.…”
Section: The Zzs Complex Shepherds Joint Molecules Toward a Pro-co Statesupporting
confidence: 90%
“…A recent study suggested the importance of the local axis-enriched context to repair DSBs by the interfering CO pathway (Medhi et al 2016). Consistently, our data identified a link between the ZZS complex and the chromosome axis.…”
Section: The Zzs Complex Shepherds Joint Molecules Toward a Pro-co Statesupporting
confidence: 90%
“…Meiosis I is a process that homologous chromosomes are segregated and joined as tetrads, producing two haploid cells. And meiosis II is the second meiotic division involving the separation of sister chromatids [1, 2]. Errors in these processes, including deficient structure of spindle and unbalanced allocation of chromosomes could lead to the generation of aneuploidy [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this prior study also provided evidence that Spo11 activity can confer on HO DSBs, in trans , an increased capacity to resolve as a crossover. Medhi et al (2016) also reported evidence in support of the idea that Spo11 increases the likelihood that an artificially-supplied meiotic DSB will repair via a “meiotic-like” crossover pathway. However, whether artificial DSBs utilize meiosis-specific crossover factors, such as MutSγ, when Spo11 is absent was not examined in prior studies.…”
Section: Discussionmentioning
confidence: 82%
“…The HO endonuclease was found to promote interhomolog crossover recombination in spo11 yeast meiosis at higher frequency than in mitotic cells ( Malkova et al 1996b ; Malkova et al 2000 ), consistent with the idea that Spo11 -independent features of the meiotic nucleus may allow DSBs to engage with chromosome pairing and/or recombination pathways that promote favorable outcomes for meiosis; an example of such a mechanism might be the interhomolog bias-promoting activity of meiosis-specific chromosome axis proteins like Red1 and Rec8 , and/or meiosis-specific recombinase machinery ( Schwacha and Kleckner 1997 ; Hong et al 2013 ). However, the presence of Spo11 has also been found to exert a positive effect on the capacity of artificially-supplied meiotic DSBs to repair as interhomolog crossovers ( Malkova et al 1996b ; Malkova et al 2000 ; Neale et al 2002 ; Medhi et al 2016 ). The extent to which Spo11 activity is uniquely engaged with and capable of driving meiotic chromosome pairing processes remains obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation